A literature review of Happiness and Economics and guide to needed research - Wiese, Thomas (Competitio, 2014)
Happiness and Economics as a new branch of behavioural economics has had a major impact on economic theory and economic policy: Several studies have been published in the last 20 years in leading journals. Furthermore, several governments have decided to collect data about the well-being of their citizens. The author claims that utility cannot only be measured by the choices individuals do: Reported happiness and life satisfaction data is also an acceptable empirical estimate for individual utility. Consequently, happiness research can bear new knowledge and important understanding of human welfare. Therefore, this paper gives an overview of the existing literature. Methods and approach of scholars is critically analysed and shortcomings are discussed. Thereafter, findings on major economic issues like growth, unemployment and inflation are presented. Besides, governmental policy and implications for society are debated. Lastly, future research possibilities are mentioned. Journal of Economic Literature (JEL) Classification: D60 D63 I31